Attack graph generation algorithm for large-scale network based on parallel - Zhao, Kai; Zhang, Yi; Lai, Ben; Li, Xiao-Xing (Tongxin Xuebao, 2011)
An attack graph generation algorithm based on parallel was presented. Firstly, the process of attack graph generation is divided into several sub-tasks, and the function of each sub-task is generating sub-attack graph between two subnets. Secondly, all the sub-tasks are handled parallel on multiple processors. Finally, form the final attack graph by integrating all the sub-attack graphs. The main ideas and work process of the algorithm were described. Theoretical analysis and experiment show that the algorithm has better scalability.